PENGARUH SERVICE EXCELLENCE DAN SERVICESCAPE TERHADAP INTENTION TO REUSE KERETA PANORAMIC - Chaniago, Putri Audriel; Widyastuti, Hardiana (Universitas Multimedia Nusantara, 2024)
Abstract - The development of the goods and services sector is increasing, especially in the transportation services sector. PT Kereta Api Pariwisata launched a new innovation, namely the panoramic train. The aim of the research is to analyze the influence of service excellence and servicescape on intention to reuse panoramic trains. PT Kereta Api Pariwisata maintains customer interest in continuing to reuse them by applying service excellence and servicescape to its products and services to remain competitive and dominate market share. The data sources used are primary data obtained by distributing questionnaires to respondents and secondary data obtained by reading scientific journals, books and other reading sources. Descriptive analysis and SEM-PLS are used as data processing methods to analyze the influence of service excellence and servicescape on intention to reuse. The results indicate that service excellence and servicescape significantly and positively influence intention to reuse panoramic train. Service excellence and servicescape play an important role in influencing passengers' intention to return to the panoramic train service. Improvements in both aspects will help increase customer loyalty and the long-term success of the panoramic train service. The managerial implications recommended by the researcher are formulated using the 7P marketing strategy approach (Product, Price, Place, Promotion, People, Process, Physical Evidence). Keywords: Intention to Reuse; Panoramic Train; Servicescape; Service Excellence